2018
DOI: 10.3171/2017.2.jns1784
|View full text |Cite
|
Sign up to set email alerts
|

Surgical intervention for pituitary apoplexy: an analysis of functional outcomes

Abstract: OBJECTIVE Pituitary apoplexy is a clinical syndrome consisting of neurological and endocrine abnormalities secondary to hemorrhage or ischemia of an underlying pituitary adenoma. The authors investigated whether there was a significant difference in neurological, endocrine, and nonneuroendocrine outcomes for patients with pituitary apoplexy, based on the time between symptom onset and surgical intervention. METHODS The authors retrospectively analyzed the medical records of 32 patients who had presented to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 35 publications
(50 reference statements)
4
41
0
Order By: Relevance
“…24 Rutkowski et al reported a gross-total resection rate of 67% in a similar cohort of patients. 25 In addition to the high-resection rate in the current series, no patients had any postoperative complications that is similar to that of other case series. 2,24 The effectiveness of the endoscopic transsphenoidal resection is best demonstrated in ►Table 2.…”
Section: Discussionsupporting
confidence: 88%
“…24 Rutkowski et al reported a gross-total resection rate of 67% in a similar cohort of patients. 25 In addition to the high-resection rate in the current series, no patients had any postoperative complications that is similar to that of other case series. 2,24 The effectiveness of the endoscopic transsphenoidal resection is best demonstrated in ►Table 2.…”
Section: Discussionsupporting
confidence: 88%
“…The median age of the patients presenting with pituitary apoplexy in our cohort was 46.7 (IQR 31.5–57.0) years, which is consistent with the mean ages (38–52 years) observed in other series ( 11 , 12 , 13 , 14 , 15 ). Pituitary apoplexy is often reported to occur more frequently in men than in women; however, we observed equal gender distribution in our series ( 6 , 11 , 14 , 15 ). All but one case of pituitary apoplexy in our series were in the context of a macroadenoma, especially non-functioning adenomas ( 5 , 10 , 18 , 19 ).…”
Section: Discussionsupporting
confidence: 90%
“…Patients with pre-existing pituitary adenoma have a 2–12% chance of pituitary apoplexy; however, pituitary apoplexy is frequently the first presentation of pituitary disease ( 1 , 4 , 6 , 11 , 12 , 13 , 14 ). Pituitary apoplexy is rare, and although described at all ages, it is most frequent in the fifth to sixth decades ( 1 , 6 , 11 , 12 , 13 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PA is a clinical syndrome consisting of endocrine abnormalities and neurological deficits caused by underlying pituitary adenoma hemorrhage and/or ischemia, resulting in expansion, edema and necrosis. 5 , 6 The clinical manifestations of PA are diverse. Anterior pituitary hormone deficiency, especially ACTH deficiency, is prone to cause electrolyte disturbances, nausea and vomiting.…”
Section: Discussionmentioning
confidence: 99%